Vascular malformations: An overview of their molecular pathways, detection of mutational profiles and subsequent targets for drug therapy - Mansur, Ann; Radovanovic, Ivan (Frontiers in Neurology, 2023)
Vascular malformations are anomalies in vascular development that portend a significant risk of hemorrhage, morbidity and mortality. Conventional treatments with surgery, radiosurgery and/or endovascular approaches are often insufficient for cure, thereby presenting an ongoing challenge for physicians and their patients. In the last two decades, we have learned that each type of vascular malformation harbors inherited germline and somatic mutations in two well-known cellular pathways that are also implicated in cancer biology: the PI3K/AKT/mTOR and RAS/RAF/MEK pathways. This knowledge has led to recent efforts in: (1) identifying reliable mechanisms to detect a patient's mutational burden in a minimally-invasive manner, and then (2) understand how cancer drugs that target these mutations can be repurposed for vascular malformation care. The idea of precision medicine for vascular pathologies is growing in potential and will be critical in expanding the clinician's therapeutic armamentarium.